VISUAL STORYTELLING ON INSTAGRAM: A CRITICAL REVIEW OF MARKETING COMMUNICATION IN THE CREATIVE ECONOMY - Ryndian Gusty; Mawaddah; Yohana Yulianti Simbolon; Arief Budiman (Smart Education, 2026)
Abstract: This study aims to analyze the role of visual storytelling (VS) in increasing user engagement on Instagram within the context of the creative economy. This study positions visual storytelling as an ideological practice rooted in affective domination, platform logic, and cultural commodification. This differs from the use of instrumental narratives that emphasize marketing effectiveness. The research method employed is a qualitative approach using critical interpretative and thematic synthesis. The analyzed literature comprises 48 articles relevant to the research objectives. The findings reveal that visual storytelling is perceived as a creative and authentic means of marketing communication. It also functions to establish mechanisms capable of exerting subtle dominance. Strategically, it leverages the potential of modified emotions, cultural identity, and creativity regulated by platform algorithms. The theoretical contribution of this research confirms that visual storytelling serves as a space for narrative dominance, where stories are reduced to instruments aligned with the interests of the market and the platform. These findings further strengthen perspectives within the literature on digital culture and critical marketing. This study also places significant emphasis on human-centered digital communication ethics, transparency, and cultural appropriateness. Therefore, the effectiveness of visual storytelling is not only measured by the level of consumer engagement, but also by its impact on equity and meaning within the creative economy ecosystem. Keywords: Visual Storytelling; Consumer Engagement; Instagram; Creative Economy Abstrak: Penelitian ini bertujuan untuk menganalisis peran visual storytelling (VS) dalam meningkatkan keterlibatan pengguna di Instagram dalam konteks ekonomi kreatif. Studi ini meletakkan visual storytelling sebagai praktik ideologis yang berakar pada dominasi afektif, logika platform, dan komodifikasi budaya. Hal tersebut memiliki perbedaan dari penggunaan narasi instrumental yang menekankan efektivitas pemasaran. Metode penelitian yang digunakan yaitu pendekatan kualitatif melalui critical interpretative dan thematic synthesis. Hasil literatur yang di analisis berjumalah 48 artikel yang sesuai dengan tujuan penelitian. Hasil temuan yang didapatkan bahwa visual storytelling dinilai sebagai cara kreatif dan asli dalam melakukan komunikasi pemasaran. Kemudian juga berfungsi untuk membentuk mekanisme yang bisa mendominasi secara halus. Secara strategis memanfaatkan potensi emosi yang dimodifikasi, identitas budaya dan kreativitas yang diatur oleh algoritma platform. Kontribusi teoritis penelitian menegaskan bahwa visual storytelling menjadi tempat dominasi naratif yang menggunakan cerita yang direduksi menjadi instrumen yang mengacu pada kepentingan pasar dan platform. Temuan ini semakin memperkuat perspektif dalam literatur budaya digital dan pemasaran kritis. Penelitian ini juga memberikan penekanan penting terhadap etika komunikasi digital yang berpusat pada diri manusia, transparansi dan kesesuaian budaya. Maka dari itu, efektivitas visual storytelling bukan hanya diukur dari tingkat keterlibatan konsumen, namun juga dari pengaruhnya terhadap keadilan dan pemaknaan dalam ekosistem ekonomi kreatif Kata Kunci: Visual Storytelling; Keterlibatan Konsumen; Instagram; Ekonomi Kreatif